Protein engineering of amine transaminases - Meng, Qinglong; Ramírez-Palacios, Carlos; Wijma, Hein J.; Janssen, Dick B. (Frontiers in Catalysis, 2022)
Protein engineering is a powerful and widely applied tool for tailoring enzyme properties to meet application-specific requirements. An attractive group of biocatalysts are PLP-dependent amine transaminases which are capable of converting prochiral ketones to the corresponding chiral amines by asymmetric catalysis. The enzymes often display high enantioselectivity and accept various amine donors. Practical applications of these amine transaminases can be hampered by enzyme instability and by their limited substrate scope. Various strategies to improve robustness of amine transaminases and to redirect their substrate specificity have been explored, including directed evolution, rational design and computation-supported engineering. The approaches used and results obtained are reviewed in this paper, showing that different strategies can be used in a complementary manner and can expand the applicability of amine transaminases in biocatalysis.